GOVERNANCE AMONG MALAYSIAN HIGH PERFORMING COMPANIES - Asri, Marsidi; Shazali, Abu Mansor (Virtus Interpress, 2016)
Well performed companies have always been linked with effective governance which is generally reflected through effective board of directors. However many issues concerning the attributes for effective board of directors remained unresolved. Nowadays diversity has been perceived as able to influence the corporate performance due to the likelihood of meeting variety of needs and demands from diverse customers and clients. The study therefore aims to provide a fundamental understanding on governance among high performing companies in Malaysia.